Petersburg to Appomattox : The End of the War in Virginia - Janney, Caroline E. (Book collections on Project MUSE., 2018)
The last days of fighting in the Civil War's eastern theatre have been wrapped in mythology since the moment of Lee's surrender to Grant at Appomattox Court House. War veterans and generations of historians alike have focused on the seemingly inevitable defeat of the Confederacy after Lee's flight from Petersburg and recalled the generous surrender terms set forth by Grant, thought to facilitate peace and to establish the groundwork for sectional reconciliation. But this volume of essays by leading scholars of the Civil War era offers a fresh and nuanced view of the eastern war's closing chapter.